Comparative Study Of The Quality Of Dried Choux Tilapia Meat - Susanti, Sri Nugroho; Faridah, Anni (Universitas Negeri Padang, 2023)
Dried choux is a choux paste dough, small in size, brownish yellow in color, crunchy textured with a savory taste.Utilization of tilapia in dried milk can add new innovations in the field of pastry.This study aimed to analyze differences in the sensory quality of dried tilapia meat and cheese. This type of research is experimental, using a completely randomized design (CRD) with two treatments and three repetitions. The products made were subjected to a sensory test by 5 limited panelists (5 lecturers) by filling out a questionnaire. The data obtained were then processed using the independent sample t-test program SPSS 25.0 to determine the differences between treatments. The results showed that the average value of the sensory test results of dry milk using cheese and tilapia meat was uniformly 3.67 and 3.60; star shape diameter 1 cm 3.27 and 3.13; colors 3.87 and 3.67; fragrance 1.07 and 2.13; hollow texture 3.87 and 3.60; and crunchy textures 3.60 and 3.53; and savory taste 3.60 and 3.53; typical taste of tilapia 1.00 and 2.00. the fragrance and taste of dried choux tilapia meat with cheese had been significant difference.